EFFECT OF hCG BEFORE, DURING AND AFTER INDUCED ESTRUS ON CONCEPTION AND PROGESTERONE IN REPEAT BREEDER COWS - SELVARAJU, M; VEERAPANDIAN, C; KATHIRESAN, D; KULASEKAR, K; CHANDRAHASAN, C (The Indian Journal of Animal Reproduction, 2023)
The repeat breeding syndrome in cows is the most commonly encountered and poorly understoodcondition causing economic loss to the farmers. A total of 64 repeat breeder cows were treated with0.98 mg of Tiaprost on day 10 following natural estrus and were equally divided into 4 groups as PGN,PG-P, PG-O and PG-E and were treated with no hCG, 1500 IU hCG at 24 hrs before first Al, at firstAl and at 4 days following first Al, respectively. Sixteen untreated repeat breeder cows served ascontrol. In the treated cows Al was done at 72 (first Al) and 96 hrs {Second Al) after PGF20 injection. Incontrol group, Al was carried out twice at 24 hrs interval in natural estrus. Blood was collected atdifferent phases of treatment for progesterone assay. First service conception rates obtained were43.75, 43.75, 62.50 and 37.50 percent in PG-N, PG-P, PG-O and PG-E, respectively and the same incontrol was18.75 per cent. The O¥erall mean level (ng/ml) of serum progesterone at the time of naturalestrus, PGF2a injection, induced estrus and at 2nd, 4th and 6th day following first Al in cows whichbecame pregnant was 0.36±0.08, 7.19±0.46, 0.18±0.05, 1.05±0.20, 1.70±0.22 and 3.37±0.77 andcorresponding values in non pregnant cows were 0.51±0.09, 5.24±0.43, 0.23±0.03, 0.57±0.15, 0.99±0.27and 1.62±0.26, respectively. It is concluded that PGF2a in combination with hCG at Al, improved theconception rate in repeat breeder cows.
Keywords: hCG administration; Conception rate; Repeat breeder cows